THU0649-HPR Variation in The Provision and Composition of Multidisciplinary Teams in Rheumatology Services across The UK: A Cross-Sectional Study. (15th July 2016) - Ndosi, M.; Ferguson, R.; Backhouse, M.R.; Bearne, L.; Ainsworth, P.; Roach, A.; Dennison, E.; Cherry, L.
Abstract : Background: Care by the multidisciplinary team (MDT) is recommended by the current treatment guidelines in the UK and elsewhere in Europe. In rheumatology the evidence to support the effectiveness of multidisciplinary working is limited. 1, 2 Furthermore, the availability of all members of the MDT in rheumatology teams across the UK is unclear. Objectives: To describe the national provision of MDT care within Rheumatology services across the UK. Methods: This was a "service" survey conducted in all rheumatology departments within the UK. In England, the survey was a part of a broader national audit for rheumatoid and early inflammatory arthritis commissioned by Healthcare Quality Improvement Partnership (HQIP). The approval to undertake this sub-analysis was gained from HQIP and supported by the British Society for Rheumatology research committee and British Health Professionals in Rheumatology. Scotland and Northern Ireland were not included in the national audit therefore a separate, but identical, survey was conducted. The design of the service survey content was agreed in consultation with the BHPR committee, which is formed of health professionals with clinical and research experience in rheumatology. The survey collected organisation data regarding the specific inclusion of, or direct access to, medical, nursing, physiotherapy, podiatry and occupational therapy practitioners as part of the MDT. Detail regarding the whole time equivalent (WTE) availability of each named speciality was recorded and summarised by region. Results: The survey response rate was 98% (164/167). Table 1 shows the overall rheumatology staffing levels measured in WTE between professional groups. All departments reported having medical staff present and almost all had a nurse but the inclusion of physiotherapists, occupational therapists and podiatrists in the MDT was variable. Only 48% of the teams surveyed had access to a podiatrist. There was a high degree of regional variation in the provision of health professionals and only 28 (17%) of the surveyed teams had all the named professional groups represented in their multidisciplinary teams. Conclusions: There is a high degree of regional variation in the composition and staffing levels of the Rheumatology MDT across the UK. Further research is required determine the most efficient configuration of the MDT in rheumatology services. References: Martínez-González NA, Berchtold P, Ullman K, et al. Integrated care programmes for adults with chronic conditions: a meta-review. Int. J. Qual. Health Care 2014;26(5):561–70. Bearne LM, Byrne AM, Segrave H, et al. Multidisciplinary team care for people with rheumatoid arthritis: a systematic review and meta-analysis. Rheumatol. Int. 2015;doi:10.1007/s00296-015-3380-4. Disclosure of Interest: None declared